Konsep Dasar Teori Hukum serta Pendekatan dalam Filsafat dan Teori Hukum - Agus Munandar (Indo Publishing, 2026)
Law plays an important role in regulating social life in order to create order, justice, and legal certainty. To understand the function and purpose of law comprehensively, it is necessary to study legal theory and philosophy of law. This research aims to explain the basic concepts of legal theory and examine various approaches in the philosophy and theory of law. The research method used is normative legal research with conceptual, philosophical, and historical approaches. Data were collected through library research using various literature sources, such as books, journals, and the opinions of legal scholars. The results of this study indicate that legal theory is a field that discusses the basic concepts of law, legal norms, sources of law, and legal principles that form the foundation for the implementation of law in society. Meanwhile, the philosophy of law focuses on moral values, justice, and the purpose of law. Various approaches in the philosophy of law, such as normative, analytical, social, historical, and philosophical approaches, provide different perspectives regarding the nature and application of law. These approaches complement one another in developing a legal system that is fair, responsive, and in accordance with societal development. Therefore, an understanding of legal theory and philosophy of law is essential in developing a legal system that not only emphasizes legal certainty but also upholds the values of justice and humanity.